PH- Mapping Of Prepubertal Skin Of Indian Subjects - Gupta A B (Wolters Kluwer Medknow Publications, 1995)
PH- mapping of skin was made by measuring the skin surface pH in 61 normal Indian subjects (35M, 26F) in the prepubertal age group at 21 different sites from scalp to sole at an ambient temperature 25-32C and a relative humidity 60-65%. The pH values at axilla, umbilicus, palm, fingerfolds, foot, sole, and cheek were found to be consistently higher than those at scalp, forehead, retroauricular folds, antecubital and popliteal fossae, anterior arm, anterior the mean pH of male skin appeared to be lower than that of female. The highest pH recorded was in axilla (5.98 for male, 6.00 for female), irrespective of sex. The lowest value however was in anterior neck (4.59) for male and in antecubital fossa (4.83) for female. While the origin of the skin pH is yet to be definitely known, it was observed that a high density of both sweat gland and bacteria flora leads to a high pH, and high concentration of sebaceous gland and of bacterial flora to a lower pH.